Pengaruh Pendidikan Agama Terhadap Perilaku Keagamaan Peserta Didik - Mukhtaruddin mukhtaruddin (Analisa: Journal of Social Science and Religion, 2011)
The curriculum of Islamic education applied in private senior high schoolsis not the same from one to another because they are permitted to implementthe curriculum legalized by the Ministry of National Education on one hand,and local curriculum (the curriculum issued by their own foundations) on theother; and the curriculum of each school has its own characteristics. The mainpurpose of this study is to determine whether there are significant differences,in terms of religious behaviours, of students who obtained a teaching curriculumdesigned by the foundations and the students who acquired learningwith curriculum legalized by the Ministry of National Education. By taking asample of 240 students from various private schools, the result of the studyshows that, in terms of religious behaviours, those who obtained a teachingwith curriculum of the foundations are better than that of students who obtainedlearning with the curriculum of the Ministry of National Education.